2020
DOI: 10.3390/ijerph17030743
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Based Differences in the Quality of Life of Elderly Koreans With Chronic Musculoskeletal Pain

Abstract: In this study, we constructed a structural equation model (SEM) for predicting the quality of life (QOL) in elderly Koreans with chronic musculoskeletal pain (CMP) and examined the differences between sexes. Data were earlier collected in a prior study of 307 participants (101 men and 206 women) with CMP, aged 65 years and above, who used geriatric welfare centers located in two cities. The effects of pain, functional limitation, perceived health status, pain coping, and social support on the QOL were estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
(47 reference statements)
0
3
1
Order By: Relevance
“…Moreover, Jeong et al found that functional limitations directly affect QoL more in men compared to women. They attributed this to the fact that men have more social roles than women, especially in Korea (1). Their results are different from those of the present study.…”
Section: N Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Moreover, Jeong et al found that functional limitations directly affect QoL more in men compared to women. They attributed this to the fact that men have more social roles than women, especially in Korea (1). Their results are different from those of the present study.…”
Section: N Discussioncontrasting
confidence: 99%
“…W ith the increase in the elderly population, the incidence of musculoskeletal diseases is also rising. Often, the spine and knee are affected, causing chronic musculoskeletal pain (1), which leads to disability and affects quality of life (QoL) (2). Osteoarthritis is one of the most common causes of chronic musculoskeletal pain and remains a significant problem for individuals and societies worldwide due to its increasing prevalence (3).…”
Section: N Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…China's aging population ranks first in the world, moreover, the problem of rapid aging in China has attracted global attention (Nie et al, 2021). Aging is further burdened with poverty, disease, disability, service and care limitations (Jeong and Lee, 2020). Currently, there are various modes of old adult care in China, including self-care, family care, institutional care, and community care.…”
Section: Introductionmentioning
confidence: 99%